Influence of positive and negative affect on self-management among patients with early chronic kidney disease during the COVID-19 pandemic: The mediating and suppressing effect of ego depletion - Cui, Yi; Li, Rong; Yang, Tianqi; Wang, Hua; Jin, Shasha; Liu, Na; Liu, Hongbao; Zhang, Yinling (Frontiers in Psychiatry, 2022)
Background: Self-management in patients with early chronic kidney disease (CKD) can effectively delay damage to renal function. However, with the continuous spread of COVID-19, patients cannot receive timely treatment, which can lead to different affects, resulting in ego depletion and serious challenges to self-management. This study aimed to investigate the mediating and suppressing roles of ego depletion on the relationship between positive and negative affect and self-management among patients with early CKD during the COVID-19 pandemic in China. Methods: A total of 383 patients with early CKD from three tertiary hospitals were enrolled by convenience sampling in our cross-sectional study from September 2021 to March 2022. Participants completed the Sociodemographic Questionnaire, Positive Affect and Negative Affect Scale, Self-Regulating Fatigue Scale and Chronic Kidney Disease Self-Management Instrument. A structural equation model was conducted to test the mediating and suppressing effects. Results: The average score of the participants’ self-management was 84.54 (SD: 19.72), and nearly 60% of them were at low and moderate levels. The mediating effect of positive affect on self-management through ego depletion was significant (β = 0.248, 95% CI: 0.170 to 0.376), accounting for 53.22% of the total effect. The suppressing effect of negative affect on self-management through ego depletion was significant (β = -0.191, 95% CI: -0.310 to -0.118), and the absolute value of the ratio of the suppressing effect to the direct effect was 66.55%. Conclusions: Ego depletion partially mediated the relationship between positive affect and self-management while suppressing the relationship between negative affect and self-management among patients with early CKD during the COVID-19 pandemic. The reduction of patients’ ego depletion must be taken as the intervention target to improve self-management and delay the progression of CKD.